Microglia, seen from the CX3CR1 angle - Wolf, Yochai; Yona, Simon; Kim, Ki-Wook; Jung, Steffen (Frontiers in Cellular Neuroscience, 2013)
Microglial cells in brain and spinal cord are characterized by high expression of the chemokine receptor CX3CR1. Expression of the sole CX3CR1 ligand, the membrane-tethered and sheddable chemokine CX3CL1/ fractalkine, is restricted in the brain parenchyma to selected neurons. Here we summarize our current understanding of the physiological role of CX3CR1 for microglia function and the CX3C axis in microglial/ neuronal crosstalk in homeostasis and under challenge. Moreover, we will discuss the efforts of our laboratory and others to exploit CX3CR1 promoter activity for the visualization and genetic manipulation of microglia to probe their functional contributions in the CNS context.